Reproductive biology of the spotted scat Scatophagus argus (Linnaeus, 1766) from Mandapam waters, south-east coast of India - Gandhi, V.; Venkatesan, V.; Ramamoorthy, N. (Indian Journal of Fisheries, 2014)
Reproductive biology of the spotted scat Scatophagus argus (Linnaeus, 1766) was studied by examining 1,659 individuals collected fortnightly between August 1995 and July 1997 from the Gulf of Mannar along Mandapam coast. Overall sex ratio (1:2.2) indicated that the population had significantly higher proportion of females than males (Ï‡2 test, p<0.05). Size at first maturity estimated was 120.5-125.5 mm (males) and 140.5-145.5 mm (females). The spawning season coincided with monsoon months and was observed to extend from June to August (south-west monsoon) with peak in July and from October to December (north-east monsoon) with peak in November. Seven stages of gonadal maturation were established based on macroscopic characteristics viz., immature, developing immature/recovering spent, maturing, mature, advanced mature, ripe and spent. The diameter of ova ranged from 0.10 to 0.75 mm. Fecundity range of 20 females was 1,15,038 in fish of size 235 mm and 265 g to 1,53,661 in fish of size 300 mm and 350 g.